2003
DOI: 10.1111/j.1939-1676.2003.tb02497.x
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Transthoracic Temporary Cardiac Pacing in Dogs

Abstract: Temporary cardiac pacing is used in the emergency treatment of life-threatening bradyarrhythmias and for the support of heart rate and blood pressure of patients with sick sinus syndrome or high-grade atrioventricular (AV) block undergoing general anesthesia, typically for permanent pacemaker implantation. We retrospectively evaluated the safety and efficacy of a noninvasive transthoracic external cardiac pacing system in 42 dogs treated for bradyarrhythmias. Optimal placement of the patch electrodes on the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
28
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 23 publications
2
28
0
1
Order By: Relevance
“…Local skeletal muscle contraction is occasional a reason for termination of TEP in human beings; modification of the electrodes and reduction of the stimulation threshold reduced its occurrence (Zoll and others 1981). DeFrancesco and others (2003) reported signs of pain and skeletal muscle contraction in all dogs studied, and found that stimulation of skeletal muscles occurred even when TEP was initiated during general anaesthesia. As reported by Lee and others (2008), placement of the pacing electrodes over the left and right fifth to seventh costochondral joint resulted in only minimal twitching of the deep pectoral muscles.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Local skeletal muscle contraction is occasional a reason for termination of TEP in human beings; modification of the electrodes and reduction of the stimulation threshold reduced its occurrence (Zoll and others 1981). DeFrancesco and others (2003) reported signs of pain and skeletal muscle contraction in all dogs studied, and found that stimulation of skeletal muscles occurred even when TEP was initiated during general anaesthesia. As reported by Lee and others (2008), placement of the pacing electrodes over the left and right fifth to seventh costochondral joint resulted in only minimal twitching of the deep pectoral muscles.…”
Section: Discussionmentioning
confidence: 96%
“…The use of TEP in clinical veterinary medicine was previously described by DeFrancesco and others (2003) in 42 dogs that underwent PMI, ophthalmic surgery, or emergency treatment for haemodynamically unstable bradyarrhythmias. In the present study, third-degree AVB was the most common indication for, in agreement with previously published data (Sisson and others 1991, Oyama and others 2001, Wess and others 2006, Johnson and others 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Defrancesco and others (2003) reported that non-invasive transthoracic temporary pacing was a successful and safe method in the management of clinically relevant bradyarrhythmias in dogs.…”
Section: Discussionmentioning
confidence: 99%